Estudio de Prefactibilidad para la Creación de un Centro de Acopio Agrícola en el Municipio de Pivijay, Magdalena. - Collazo Collazos, Jesús Iván; Quintero Campo, Néstor Eduardo (Universidad Antonio Nariño, 2022)
Pre-feasibility study for the creation of an agricultural collection center in the municipality of Pivijay, Magdalena as part of the preliminary degree project for the Antonio Nariño University. The study will be carried out in this location because the municipality has an ejido which is the Agricultural Epicenter of the Magdalena department. In this way, the agricultural products produced by the municipality will be focused on this collection center for after they are marketed. The implementation of this study seeks to transform a need into an entrepreneurial option, guaranteeing a socioeconomic benefit for the population through this collection center a municipal level, a departmental and national future.